"Aging", sessualità e cinema nella cultura italiana del secondo dopoguerra (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
Special issue on "aging" and sexuality in the Italian culture.
Keywords: Aging; Sexuality; Italian cinema